So near yet so far the public and hidden worlds of Canada-US relations - Hale, Geoffrey E. 1955- (UBC Press, 2012)
"How do politicians, diplomats, and interest groups negotiate the tangled web of Canada-US relations? So Near Yet So Far provides in-depth look at the multiple dimensions of this complex relationship, especially in the period since 9/11. It bridges the traditional gap between academic perspectives and those of diplomatic, policy, and government relations professionals to explore both the similarities and very significant differences between the two countries political systems and why both matter to anyone trying to understand or influence policy outcomes in both countries
Includes bibliographical references (p. [384]-409) and index
Keywords: Außenpolitik; Canada / Foreign relations / United States; United States / Foreign relations / Canada; Canada / Foreign relations / 1945-; United States / Foreign relations / 2001-; Canada / Relations extérieures / États-Unis; États-Unis / Relations extérieures / Canada; Canada / Relations extérieures / 1945-; États-Unis / Relations extérieures / 2001-; Kanada; USA